37 Reducing overtreatment of early stage ovarian cancer: strategies implementation by a mirna-driven prognostic assessment. (18th September 2019) - Ditto, A; Raspagliesi, F; Leone Roberti Maggiore, U; Chiappa, V; Bogani, G; Liberale, V; Evangelista, MT; Sonetto, C; Maltese, G; Zanaboni, F; Carcangiu, ML; Paolini, B; et al.
Abstract : Objectives: About 30% of Epithelial Ovarian Cancer (EOC) patients present with early-stage disease (FIGO stage I–II). However, in spite of the generally favourable prognosis, eEOC have heterogeneous risk of relapse, ranging from 13% to over 40% in various reports. We previously identified 35 miRNAs that predicted risk of progression or relapse in advanced EOC and used them to create a prognostic model, the 35-miRNA-based predictor of Risk of Ovarian Cancer Relapse or progression (MiROvaR). The aim of the current study is to test MiROvaR performance to predict risk of progression or relapse in patients with eEOC. Methods: Patients with eEOC who underwent primary surgery at our Institution between 1994 and 2014 were included. The primary endpoint was progression-free survival. In particular, it was assessed the ability of MiROvaR to predict progression-free survival with Kaplan-Meier curves and the log-rank test. Results: A total of 80 patients were included in the study with a median follow-up time of 68.2 months (CI: 61.3–80.7). MiROVaR classified 37 patients (46.3%) at high-risk (14 events, median PFS: 117 months, 95%CI: 62-nyr ) and 43 patients (53.7%) at low-risk of relapse (2 events, median PFS time: nyr; 95%CI:nyr ). Kaplan-Meier curves confirmed the significantly different PFS time (figure 1 ) for the two groups with HR=10.13 (95%CI: 2.3–4.4, p=0.00015) for the high-risk patients. Conclusions: MiROvaR confirmed as a potential predictor of EOC progression and has prognostic value independent of relevant clinical covariates also in patients with eEOC. MiROvaR warrants further investigation for the development of a clinical-grade prognostic assay.